Optimization of enzymatic clarification of sapodilla juice using response surface methodology - Sin, Hwee Nee; Yusof, Salmah; Sheikh Abdul Hamid, Nazimah; Abd. Rahman, Rakmi (Elsevier, 2006)
Response surface methodology is a statistical procedure frequently used for optimization studies. It uses quantitative data from an appropriate experimental design to determine and simultaneously solve multivariate problems. In this study, a two-factor central composite design was used to establish the optimum conditions for enzymatic clarification of sapodilla juice. Sapodilla juice was treated with pectinase enzyme at different incubation times (30–120 min), temperature (30–50 °C) and enzyme concentration (0.03–0.10%). These three factors were used as independent variables whose effects on turbidity, clarity, viscosity and colour (L values) were evaluated. Significant regression models describing the changes of turbidity, clarity, viscosity and colour (L values) with respect to the independent variables were established, with the coefficient of determination, R2, greater than 0.8. The results indicated that enzyme concentration was the most important factor affecting the characteristics of the juice as it exerted a significant influence on all the dependent variables. The recommended enzyme clarification condition was 0.1% enzyme concentration at 40 °C for 120 min.